2020
DOI: 10.1039/c9gc03950c
|View full text |Cite
|
Sign up to set email alerts
|

Methanol-based acetoin production by genetically engineeredBacillus methanolicus

Abstract: Establishment of sustainable technology for methanol-based production of acetoin by metabolically engineered Bacillus methanolicus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 89 publications
2
20
0
Order By: Relevance
“…Even though several genetically engineered Bacilli have been constructed for various industrial applications (Wang et al, 2006 ; Drejer et al, 2020 ), the bioremediation applications of genetically engineered Bacilli is very limited. Huang et al ( 2015 ) constructed a genetically engineered B. subtilis 168 expressing the arsenite S-adenosylmethionine methyltransferase gene of thermophilic algae for bioremediation of arsenic.…”
Section: Advanced Technologies For Bioremediation Of Xenobiotic Compomentioning
confidence: 99%
“…Even though several genetically engineered Bacilli have been constructed for various industrial applications (Wang et al, 2006 ; Drejer et al, 2020 ), the bioremediation applications of genetically engineered Bacilli is very limited. Huang et al ( 2015 ) constructed a genetically engineered B. subtilis 168 expressing the arsenite S-adenosylmethionine methyltransferase gene of thermophilic algae for bioremediation of arsenic.…”
Section: Advanced Technologies For Bioremediation Of Xenobiotic Compomentioning
confidence: 99%
“…4 ; black bars), the fluorescence from the control strain was strongly reduced in comparison to induced conditions (> 85% reduction), however some background expression was still detectable. It has previously been reported that the xylose inducible promoter is not tightly regulated in B. methanolicus , resulting in background expression [ 83 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Methanol is an attractive carbon source for biotechnological application and natural methylotrophs have successfully been used to produce valuable products, such as amino acids or fine chemicals [10]. Selected strains of B. methanolicus secreted up to 70 g/L of l-glutamate or 35 g/L of l-lysine in high-temperature fed-batch cultivations solely from methanol and the l-lysine/l-glutamate derived products cadaverine and gamma-aminobutyric acid have since been added to extend the product spectrum [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%